2020
DOI: 10.1088/1674-1056/ab829b
|View full text |Cite
|
Sign up to set email alerts
|

Oblique collisional effects of dust acoustic waves in unmagnetized dusty plasma

Abstract: Effects of oblique collisions of the dust acoustic (DA) waves in dusty plasma are studied by considering unmagnetized fully ionized plasma. The plasma consists of inertial warm negatively charged massive dusts, positively charged dusts, superthermal kappa distributed electrons, and isothermal ions. The extended Poincaré–Lighthill–Kuo (ePLK) method is employed for the drivation of two-sided Korteweg–de Vries (KdV) equations (KdVEs). The KdV soliton solutions are derived by using the hyperbolic secant method. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…[12,20,21] Thus, when the distance between the grains is large (small), the interaction force is attractive (repulsive). [16][17][18][19][20][21] It should be mentioned that other grain-grain interaction models [3,4,12,13] can also lead to qualitatively similar results, as long as the model includes both attractive and repulsive interaction regime.…”
Section: Formulationmentioning
confidence: 84%
See 1 more Smart Citation
“…[12,20,21] Thus, when the distance between the grains is large (small), the interaction force is attractive (repulsive). [16][17][18][19][20][21] It should be mentioned that other grain-grain interaction models [3,4,12,13] can also lead to qualitatively similar results, as long as the model includes both attractive and repulsive interaction regime.…”
Section: Formulationmentioning
confidence: 84%
“…[1] The grain-grain interaction force, which is attractive at larger distances due to a unique graingrain shadowing effect, and repulsive at smaller distances due to electrostatic repulsion, plays an important role in the growing and evolving of dust grains, and can lead to many interesting, unusual, as well as practical phenomena. [3,4,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Recently it has been shown that by tailoring the external force one can obtain controllable compact structures such as dust-grain crystals, [26,27] and the time required to reach the cluster state decreases with external force increasing. [28][29][30][31][32][33] Although what happens after the external force has been withdrawn can be important in many applications, [1] it has not been investigated.…”
Section: Introductionmentioning
confidence: 99%